Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1097/00005768-199805000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate concentrations during incremental exercise in subjects with sickle cell trait

Abstract: The aim of the present study was to assess blood lactate concentrations ([LA], mmol x L(-1)) and oxygen uptake (VO2, L x min(-1), mL x kg(-1) x min(-1)) during incremental exercise in subjects with sickle cell trait (SCT) only, i.e., sedentary subjects with SCT without anemia and/or associated alpha thalassemia. Anemia was ruled out using hemoglobin (Hb) level, and alphathalassemia was ruled out using hemoglobin S (HbS) percentage and concomitant Hb level and mean corpuscular volume (MCV). Comparison was made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
6
21
1
Order By: Relevance
“…In the Gulf region, including Oman, the SCD is the most prevalent genetic blood disorder and it has been reported that 6% of the population are sickle cell gene carriers (traits) [10]. Although previous studies showed a normal exercise tolerance in adult and adolescent HbS carriers [11][12][13], meager data are available on children. Furthermore, although children with sickle cell disease (SCD) or sickle cell trait (SCT) are usually encouraged to be physically active and participate in sport and exercise on a regular basis, no information exists on the anthropometrical characteristics and exercise performance in these children in Sultanate of Oman.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gulf region, including Oman, the SCD is the most prevalent genetic blood disorder and it has been reported that 6% of the population are sickle cell gene carriers (traits) [10]. Although previous studies showed a normal exercise tolerance in adult and adolescent HbS carriers [11][12][13], meager data are available on children. Furthermore, although children with sickle cell disease (SCD) or sickle cell trait (SCT) are usually encouraged to be physically active and participate in sport and exercise on a regular basis, no information exists on the anthropometrical characteristics and exercise performance in these children in Sultanate of Oman.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have reported higher [La] during the last two increments of a graded test (12), but this contrasting result may be explained by a heterogeneous training status and differences in physical fitness between the tested subjects (12). Bile et al (1) and Sara et al (24) noted a significantly lower blood [La] during a ramp exercise test in sedentary and trained AS, respectively. In these studies, AS were carefully matched with a control group for physical activity and physiological performance (1,24).…”
Section: Discussionmentioning
confidence: 99%
“…Bile et al (1) and Sara et al (24) noted a significantly lower blood [La] during a ramp exercise test in sedentary and trained AS, respectively. In these studies, AS were carefully matched with a control group for physical activity and physiological performance (1,24). Based on the "lactate shuttle" mechanism (4, 5), the pathophysiological process involved in the lowered lactate in AS subjects during incremental exercise could be due to both greater uptake by RBCs and greater utilization by muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations